Influência do estresse por frio em pré-colheita na qualidade tecnológica de feijão comum armazenado - Kulzer, Sara Regina (2012)
The common bean has great nutritional and economic importance in Brazil. It has high protein content, being a balanced food, rich in iron, calcium, vitamins, carbohydrates, fiber and lysine, representing the basis of Brazilian food. From a physiological point, it can be considered a culture with high requirement on climate conditions, and it is considered highly sensitive to frost, since it already suffers damage from temperatures lower than 4 °C. In this study, it was evaluated the technological quality of the beans, subjected to thermal stress by cold after physiological maturity, during storage environmental conditions for 0, 30, 60 and 90 days. Factors such as color, moisture content, percentage of soaking, volumetric expansion, percentage of whole grains, tannins, proteins and cooking time were evaluated. Statistical analysis consisted of analysis of variance and Tukey comparison test at 5% significance. No significant differences were found among treatments in soaking, tannins and cooking time. Regarding the color, brightness showed significant differences for time with no difference between treatments. The protein suffered a decrease in time, but there was no influence of frost. It was concluded that thermal stress by cold after physiological maturity did not affect the beans technological quality.